To your eternity. 7 - Oima, Yoshitoki (Kodansha Comics, an imprint of Kodansha USA Publishing, LLC, 2018)
After Pioran's death, Fushi lives alone on a desert island. One day, a girl named Hisame--a descendant of a former enemy--arrives to lead Fushi to a village once destroyed by Nokkers. When Fushi reenters society, he learns he has become central to the legend of the Immortal, whom some seek, and others fear...